Tanggung Jawab Hukum dalam Pengawasan Tenaga Medis Tinjauan Kasus Dokter Gadungan Susanto - Roy Richardo Hutagaol (Jurnal Syntax Admiration, 2025)
Identity fraud and document falsification in the healthcare sector pose significant threats to professional integrity and patient safety. This study examines the case of Susanto, an impostor doctor who practiced for three years at Primasatya Husada Citra (PHC) Hospital in Surabaya, and analyzes the legal framework overseeing such incidents. The research employs a normative juridical method with a qualitative approach to explore legal aspects, identify weaknesses in medical personnel supervision systems, and propose necessary policy recommendations. The findings reveal that the Surabaya District Court’s decision to impose a four-year prison sentence on the defendant under Article 378 of the Indonesian Penal Code represents a firm legal stance aimed at deterrence. Furthermore, the study highlights that insufficient oversight by medical committees is a key factor contributing to serious breaches within the healthcare system. Therefore, enhanced audit mechanisms and evaluations in medical personnel recruitment processes are urgently needed to prevent similar incidents in the future. This research is relevant to the development of policies and practices in Indonesia's healthcare sector, particularly in strengthening the oversight mechanisms for medical personnel recruitment.